2015
DOI: 10.5812/ircmj.17(4)2015.24959
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin Levels Correlation With Heart and Liver MRI and LIC in Patients With Transfusion-Dependent Thalassemia

Abstract: Background:Iron-loaded cardiac complication is the essential cause of mortality in patients with thalassemia. Early detection and treatment of cardiac over-load can reduce mortality.Objectives:The current study aimed to evaluate the relationship between serum ferritin levels and T2* magnetic resonance imaging (MRI) of heart and liver and liver iron concentration (LIC) to diagnose iron over load in countries with limited access.Patients and Methods:In the current cross-sectional study, 85 Iranian patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
22
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 19 publications
6
22
3
Order By: Relevance
“…In this study, only 10% of studied cases (4/40) developed iron-loaded heart with either mild (5%; n = 2) or moderate (5%; n = 2) cardiac siderosis which is much less than those reported by Majd et al [31] Fig . 6 Coronal images of the liver and heart at 8 different TE (1.6-18.7ms) reveal a significant decay in both hepatic and myocardial signal that increases on longer TE imaging sequences.…”
Section: Discussioncontrasting
confidence: 62%
“…In this study, only 10% of studied cases (4/40) developed iron-loaded heart with either mild (5%; n = 2) or moderate (5%; n = 2) cardiac siderosis which is much less than those reported by Majd et al [31] Fig . 6 Coronal images of the liver and heart at 8 different TE (1.6-18.7ms) reveal a significant decay in both hepatic and myocardial signal that increases on longer TE imaging sequences.…”
Section: Discussioncontrasting
confidence: 62%
“…The incidence of abnormal cardiac T2* (<20 ms) among the subjects was lower than that mentioned in other published studies from other countries. A study in Hong Kong found 50% abnormal cardiac T2* [23], and another study in Iran obtained a value of 58% [24]. Our study showed that serum ferritin level had statistically significant correlation with liver and cardiac T2*, and as previously stated, this had little clinical value to determine cardiac and hepatic risk.…”
Section: Discussioncontrasting
confidence: 37%
“…Majd et al, [18] showed that serum ferritin has statistically significant positive correlation with LIC and significant negative correlation with T2* of Liver which agreed with our results. However, these correlations became non significant when the SF was above 4000ng/ml; among our patients there were ten patients with very high SF level above 4000ng/ml including one case with mild LIC and two cases with moderate LIC.…”
Section: Discussionsupporting
confidence: 93%